2020
DOI: 10.2147/hiv.s276356
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chronic Kidney Disease and Associated Factors Among HIV/AIDS Patients on HAART in Ethiopia</p>

Abstract: Background: In developing countries, both opportunistic infections and chronic diseases account a high HIV-associated mortality and morbidity. Chronic kidney disease (CKD) associated with HIV infection has got increased attention in sub-Saharan Africa as a result of the high HIV prevalence and due to the late diagnosis and initiation of HAART. Thus, this study was conducted to assess CKD and associated factors among HIV patients on HAART in Ethiopia. Methods: A hospital-based cross-sectional study with a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…29 Thus, determining the prevalence and contributing factors for different comorbidities such as CKD is important to improve the quality of life and long-term healthcare management of PLHIV. 30 Despite there are some studies conducted in other parts of Ethiopia, [31][32][33] still there is a paucity of studies related to CKD and its predictors among HAART naïve and HAART experienced HIV patients in this study area. Therefore, this study aimed to determine the prevalence of CKD and associated factors among HAART naïve and HAART experienced HIV-infected individuals at the selected Hospitals (Bonga G/tsadik Shawo General Hospital, Mizan Tepi University Teaching Hospital (MTUTH) and Tepi General Hospital), Southwest Ethiopia.…”
Section: What Is Already Known On This Topicmentioning
confidence: 84%
“…29 Thus, determining the prevalence and contributing factors for different comorbidities such as CKD is important to improve the quality of life and long-term healthcare management of PLHIV. 30 Despite there are some studies conducted in other parts of Ethiopia, [31][32][33] still there is a paucity of studies related to CKD and its predictors among HAART naïve and HAART experienced HIV patients in this study area. Therefore, this study aimed to determine the prevalence of CKD and associated factors among HAART naïve and HAART experienced HIV-infected individuals at the selected Hospitals (Bonga G/tsadik Shawo General Hospital, Mizan Tepi University Teaching Hospital (MTUTH) and Tepi General Hospital), Southwest Ethiopia.…”
Section: What Is Already Known On This Topicmentioning
confidence: 84%
“…A randomized trial conducted by the SMART study group indicated the renal events rate declined significantly when the patients were treated following the standard guidelines and achieved sustained viral suppression [32]. And recent research shows patients with HIV viral load more than 1000 copies/ml had over three times the risk of CKD compared with undetectable viral load [21]. There is a counterintuitive finding that participants with an initial CD4 þ cell count between 200 and 350 cells/ml were more likely to develop CKD compared with their counterparts who had an initial CD4 þ cell count less than 200 cells/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known of CKD incidence in Southern states of the USA. Second, the majority of studies are restricted to examining the risk factors at a single timepoint [21], while risk factors such as different ART eras and aging process have evolved over time. Third, a number of studies used single or only baseline measurements of HIV-related factors [9] due to the short follow-up time or restriction of data collection, which lacks sufficient longitudinal measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Current study had few limitations, no baseline renal function was done to evaluate the change in renal function over time thereby allowing for short-term impairment that may be reversible. Also, microalbuminuria was not evaluated, as it has been demonstrated to be a vital indicator for renal dysfunction identification in HIV-infected individuals 24,25 .…”
Section: Discussionmentioning
confidence: 99%